Supplementation with honeysuckle extract improves growth performance, immune performance, gut morphology, and cecal microbes in geese - Li, Guangquan; Wang, Xianze; Liu, Yi; Wang, Cui; Yang, Yunzhou; Gong, Shaoming; Zhu, Lihui; He, Daqian; Wang, Huiying (Frontiers in Veterinary Science, 2022)
To investigate the effect of honeysuckle extract (HE) on growth performance, serum biochemical indexes, immune organ indexes, gut morphology and gut microbes in geese.A total of 180 28d Holdobaki geese were divided into 3 groups randomly, Each group contains 6 replicates (10 geese, half male and female).The BD group was fed the basal diet, the HE1 group was supplemented with 1g/kg HE in the basal diet, and the HE2 group was supplemented with 2g/kg. The experiment lasted for 42 d.The results showed that: Compared with BD, the average daily gain (ADG) of HE1 and HE2 had a tendency to increase (0.05